Mobile Application Get Nurse Sebagai Platform Digital Pelayanan Kesehatan Masa Pandemi Covid-19 - Oleh Soleh; Trie Mayhera Sabalidowati; Praditya Aliftiar (UNIVERSITAS RAHARJA, 2021)
In 2020, the whole world was hit by an epidemic of COVID-19 (coronavirus diseases-19). This creates new habits and changes the pattern of people's lives. Many people are worried that they will catch the virus if they go to places such as clinics or hospitals to get health services. The community has become more vigilant and is looking for safer alternative health services. Due to this concern, the authors created a digital platform for health services that can be accessed by the public easily and quickly. This study aims to create a digital platform to bridge people who need health services without having to leave the house with health workers, especially nurses. The Business Model Canvas (BMC) is used by the author as a system analysis method. System modeling uses the Unified Modeling Language (UML). To design the system, Kotlin is used as a programming language with an MVP (Model-View-Presenter) architecture and MySQL as a database. As well as the Usability Testing method used to test the system. The result of this research is the creation of a mobile platform that can easily help people whenever and wherever they need health services.